(untitled) (Research, Society and Development, 2022)
Objective: To characterize the nutrition and cardiovascular risk aspects of HIV-infected patients admitted to a referral hospital in Belém of Pará. Methods: This is an observational, cross-sectional qualitative and quantitative study. A clinical form was prepared for the research, a structured questionnaire, to collect socioeconomic data, lifestyle, measurement of anthropometric variables, and a test "How is your diet?" to characterize the nutrition habits of HIV-infected admitted to a referral hospital in Belém-PA. Results: The sample, 60 individuals with a mean age of 19 at 34 years, presented male majority (70%) and incomplete middle education (45%). The nutritional status documented by body mass index (BMI) was principally eutrophic, followed by malnutrition documented in arm circumference (AC) and triceps skinfold thickness (TSF) measurements of the general sample. Conclusion: The individuals research was in a socioeconomic vulnerability, showed prevalence of malnutrition and intermediary classification for healthy eating. The importance of nutritional monitoring for the maintenance of nutritional status.